INNER PEACE DALAM HADIS NABI: Reaktualisasi Nilai Spiritualitas Islam bagi Generasi Z Perspektif Spiritual-Psikologi - Mu Ida Nur Fadhilah; Nasrulloh Nasrulloh (DIRAYAH : Jurnal Ilmu Hadis, 2025)
The phenomenon of increasing anxiety, overthinking, and inner anxiety in Generation Z indicates a psychological crisis rooted in the loss of meaning in life. This research aims to examine how the values of the Prophet's hadith can provide a spiritual-psychological foundation for peace of mind through the hermeneutical approach Ma'na-Maghza. This method is used to read three hadiths that are relevant to the themes of sakīnah, patience-gratitude, and tauhid-tawakkal, by emphasizing the understanding of the literal meaning as well as its universal message. This research is qualitative with content analysis of hadith texts and the integration of contemporary psychological studies on meaning-making, emotion regulation, and social connectivity. The results show that Generation Z's peace of mind can be built through three main pillars: first, collective spiritual connectedness that overcomes digital isolation; second, patience and gratitude-based emotion regulation that functions as a reframing strategy to face life stress; and third, strengthening the meaning of life through the values of monotheism and tawakkal which foster hope. The reactualization of these three prophetic values can be applied in the form of spiritual communities, Islamic mental health modules, and meaning-based psychological counseling. Thus, this study emphasizes that the integration of hadith values with modern psychological approaches can be a comprehensive solution to the problem of peace of mind in Generation Z.